Correction to: MiR-139-5p inhibits migration and invasion of colorectal cancer by downregulating AMFR and NOTCH1 - Song, Mingxu; Yin, Yuan; Zhang, Jiwei; Zhang, Binbin; Bian, Zehua; Quan, Chao; Zhou, Leyuan; Hu, Yaling; Wang, Qifeng; Ni, Shujuan; Fei, Bojian; Wang, Weili; et al. (Protein & cell, 2021)
In the original publication the display of Fig. 1 is incorrect. The correct figure is available in this correction.